Pediatric oncology a comprehensive guide - Imbach, Paul; Kühne, Thomas (Thomas R.); Arceci, Robert (Springer eBooks., 2011)
This is the second edition of a well-received compendium of information and guidance on the diagnosis and management of the various oncological diseases that are encountered in children and adolescents. For each disease entity, fundamental facts are provided that will be relevant for a range of professionals hospital physicians, specialist nurses, psycho-oncologists, physiotherapists, family doctors, and pediatricians. Compared with the first edition all chapters have been updated. Throughout, rapid orientation is ensured by the clear, consistent layout and the concise, lucid style. Pediatric Oncology: A Comprehensive Guide is an excellent, easy-to-use reference that belongs on the shelf of every practitioner who encounters or treats malignancies in the pediatric age group. Pediatric Oncology is teamwork! Fundamental facts for all those involved in diagnosis and management even social worker, pedagogic teachers, religious care persons.